2018
DOI: 10.1007/s00775-018-1604-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the lanthanide-dependent methanol dehydrogenase XoxF from the methanotroph Methylomicrobium buryatense 5GB1C

Abstract: In methylotrophic bacteria, which use one-carbon (C1) compounds as a carbon source, methanol is oxidized by pyrroloquinoline quinone (PQQ)-dependent methanol dehydrogenase (MDH) enzymes. Methylotrophic genomes generally encode two distinct MDHs, MxaF and XoxF. MxaF is a well-studied, calcium-dependent heterotetrameric enzyme whereas XoxF is a lanthanide-dependent homodimer. Recent studies suggest that XoxFs are likely the functional MDHs in many environments. In methanotrophs, methylotrophs that utilize methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 53 publications
3
61
0
3
Order By: Relevance
“…The large number of hydrophobic residues in the putative ligand‐binding region of XoxJ is a shared feature of the active sites of MDHs. In MDHs, the PQQ cofactor is stacked between a conserved tryptophan residue and an unusual disulfide bond that forms between adjacent cysteine residues (Figure S9) . Given the presumed necessity of a PQQ chaperone, we considered PQQ as a potential ligand for XoxJ, which also contains a tryptophan side chain in the central cavity (Trp200, Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The large number of hydrophobic residues in the putative ligand‐binding region of XoxJ is a shared feature of the active sites of MDHs. In MDHs, the PQQ cofactor is stacked between a conserved tryptophan residue and an unusual disulfide bond that forms between adjacent cysteine residues (Figure S9) . Given the presumed necessity of a PQQ chaperone, we considered PQQ as a potential ligand for XoxJ, which also contains a tryptophan side chain in the central cavity (Trp200, Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…These observations indicate that removing the cofactor disrupts the dimer interface, and implies that the reverse reaction, cofactor insertion, should be accompanied by an ordering of this region of the protein and dimerization. Based on conserved structures of MDHs in general, and a homology model of M. extorquens XoxF derived from the X‐ray structure of M. fumariolicum XoxF, more specifically, we speculate that the C terminus of the protein may undergo the most significant conformation change upon holoenzyme assembly. This region forms a helical domain that clamps over the active site, near the PQQ cofactor, in the homology model template structure (Figure S13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7a] This extra ligandi sa ble to satisfy the higherc oordination number preferenceo ft he Ln 3 + ion compared to Ca 2 + .I th as been reported that XoxF-MDHs show highera ffinity and catalytic activity towardsaw ide range of primary alcohols compared to the MxaFI-MDHs due to the stronger Lewis acid characteristics of the Ln 3 + ion. [12] The field of lanthanide-dependent bacterial metabolism is quicklyg rowing. [7a, 10] Among XoxF-MDHs, in the present study we were particularly interested in the Eu 3 + dependent MDH from Methylacidiphilum fumariolicum SolV.V ery recentlyt he crystal structures of this MDH wered etermined in the presence of Eu 3 + and Ce 3 + .…”
Section: Introductionmentioning
confidence: 99%
“…In diesem Fall war die Elektronendichte im PQQ-basierten Molekülorbital über das aromatische System Abbildung 4. Vergleich der aktiven Zentren von Ca-MDH [32] (M. extorquens,P DB:1 W6S) und La-MDH [31] (Mm. buryatense,P DB:6 DAM).…”
Section: Modellierung Des Aktiven Zentrums In Xoxf -Strukturchemie Ununclassified